Urban Parking Assessment along Major Commercial Corridors of Mahendranagar Bazaar - Joshi, Aadarsh; Mahara, Aakash; Bhatta, Aayush; Bohara, Hemant Bahadur; Raikhola, Hemant Singh; Dhami, Khadak Singh; Bhatt, Rashmi; Bohara, Birendra Kumar; Bist, Trilok Chandra (Journal of Engineering Technology and Planning, 2025)
Effective parking management is crucial for sustainable urban mobility in rapidly growing cities like Mahendranagar Bazaar, Nepal. This study examines parking patterns, focusing on legal and illegal practices of two-wheelers and four-wheelers in the central commercial hub, and their impact on traffic congestion, safety, and urban infrastructure. Using fixed-period sampling over two days (working day and weekend) across five major lanes, data were collected at 1.5-hour intervals from 9:30 AM to 5:00 PM, recording vehicle types, parking legality, occupancy, and parking adequacy. A questionnaire survey complemented these observations, capturing user perspectives on behavior, awareness, enforcement, and safety. Findings reveal that while two-wheeler parking spaces are generally sufficient, illegal parking dominates, exceeding legal parking by 20–40% across most time slots, particularly on weekends, with parking adequacy reaching 250–330%. Four-wheelers and goods vehicles lack designated spaces, exacerbating congestion and safety risks. Key issues include poor signage, weak enforcement (only 18% of users fined), low awareness (16% unaware of legal zones), and miscommunication among authorities. The study recommends multi-level parking infrastructure, clear signage, smart parking technologies, enhanced enforcement, and public awareness campaigns to improve compliance and urban functionality. These strategies aim to reduce congestion, enhance safety, and support sustainable urban planning in Mahendranagar Bazaar, offering a replicable model for mid-sized Nepalese cities pursuing Sustainable Development Goals.